Results obtained after HPV DNA and E6/E7mRNA detection accompanied by IL-10 592C/A detected genotypic variants. - Sotirija Duvlis; Drage Dabeski (My University, 2022)
Supporting dataset for the paper HPV E6/E7mRNA association with Interleukin 10 (rs1800872) variant in a group of Macedonian women
Explanation of columns from the excel document: a) In Sheet - cases: the firs column describes the results after sample testing for HPV DNA positivity defined as type of HPV that is detected and at the same time it is confirmation of HPV positivity the second column describes the result after performed HPV E6/E7 mRNA testing defined as positive or negative the third column describes the genotype of IL-10 -592 C/A variant obtained after RFLP analyses. The results are defined as AA or TT or TA variant b) in sheet - controls the first Colum describes cytological and histological status of the women after performing cytological or histological analyses the second column describes the HPV DNA status after HPV DNA and HPV E6/7 mRNA testing. The control group is consisted only of HPV negative women. the third column describes the genotype of IL-10 -592 C?A variant obtained after RFLP analyses. The results are defined as AA or TT or TA variant